How Iranian Medical Trainees Approach their Responsibilities in Clinical Settings; A Grounded Theory Research - Asemani, Omid (Iran J Med Sci, 2015)
BACKGROUND: It seems we are now experiencing “responsibility problems” among medical trainees (MTs) and some of those recently graduated from medical schools in Iran. Training responsible professionals have always been one of the main concerns of medical educators. Nevertheless, there is a dearth of research in the literature on “responsibility” especially from the medical education point of view. Therefore, the present study was carried out with the aim of presenting a theoretical based framework for understanding how MTs approach their responsibilities in educational settings. METHOD: This qualitative study was conducted at Shiraz University of Medical Sciences (SUMS) using the grounded theory methodology. 15 MTs and 10 clinical experts and professional nurses were purposefully chosen as participants. Data was analyzed using the methodology suggested by Corbin and Strauss, 1998. RESULTS: “Try to find acceptance toward expectations”, “try to be committed to meet the expectations” and “try to cope with unacceptable expectations” were three main categories extracted based on the research data. Abstractly, the main objective for using these processes was “to preserve the integrity of student identity” which was the core category of this research too. Moreover, it was also found that practically, “responsibility” is considerably influenced by lots of positive and negative contextual and intervening conditions. CONCLUSION: “Acceptance” was the most decisive variable highly effective in MTs’ responsibility. Therefore, investigating the “process of acceptance” regarding the involved contextual and intervening conditions might help medical educators correctly identify and effectively control negative factors and reinforce the constructive ones that affect the concept of responsibility in MTs.